A miniature photoelectrochemical sensor based on organic electrochemical transistor for sensitive determination of chemical oxygen demand in wastewaters. (1st May 2016) - Liao, Jianjun; Lin, Shiwei; Zeng, Min; Yang, Yue
Abstract: A three-electrode configuration is often required in the conventional photoelectrochemical measurements. Nevertheless, one common drawback is the reference electrode and the counter electrode used in the measurements, which has been proved to be an impediment for the miniaturization. In this study, a simple, cost-effective and miniature photoelectrochemical sensor based on high sensitive organic electrochemical transistor (OECT) is developed and used for the determination of chemical oxygen demand (COD) in wastewaters. The devices show detection limit down to 0.01 mg/L COD, which is two orders of magnitude better than that of the conventional photoelectrochemical method. The excellent sensing performance can be contributed to the novel sensing mechanism of OECT devices. That is, the devices are sensitive to the potential changes induced by the photoelectrochemical reaction on TiO2 nanotube arrays gate electrodes. Real sample analyses are also carried out. The results demonstrate that the measured COD values using the OECT devices and the standard dichromate methods are in a good agreement. Since the proposed sensor is constructed on a miniature transistor, it is expected that the device shows a promising application on the integrated COD monitoring platform. Graphical abstract: Highlights: OECT-based photoelectrochemical sensors are constructed on miniature transistors. OECTs show lower detection limit in COD sensing. OECTs are sensitive to the potential changes on the Pt-NPs/TNTAs gate electrodes.